Identification of citrullinated fibrinogen peptides as T cell epitopes in humanised HLA-DR4 transgenic mice. (22nd February 2011) - van Heemst, J; Feitsma, AL; van der Voort, EIH; Toes, RE; Ioan-Facsinay, A
Abstract : Background: Antibodies directed against citrullinated proteins (ACPAs) are highly specific for rheumatoid arthritis (RA). The production of ACPAs is most likely dependent on the presence of T cells, since ACPAs undergo isotype switching and are associated with the shared epitope–containing HLA-DRB1 alleles. Fibrinogen is a likely candidate protein for T cell recognition, since a large subset of patients is positive for ACPAs that are reactive with (peptides derived from) citrullinated fibrinogen. Objectives: The aim of this study was to identify citrullinated fibrinogen peptides that are presented to HLA-DRB1*0401-restricted T cells. Methods: HLA-DR4-transgenic mice were immunised with citrullinated fibrinogen and T cell proliferation against all possible citrullinated fibrinogen peptides derived from the α, β, γ chain was analysed. Results: T cell reactivity against several different citrullinated fibrinogen peptides was observed. Discussion: Ongoing research is aimed at determining whether these responses are citrulline-specific and whether there is reactivity against the identified citrullinated peptides in PBMCs of RA patients.